2020
DOI: 10.1029/2020ja028205
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study on the Origin of Near‐Earth Plasma

Abstract: This study presents simulations of the coupled space environment during a geomagnetic storm that separates the different sources of near-Earth plasma. These simulations include separate fluids for solar wind and ionospheric protons, ionospheric oxygen, and the plasmasphere. Additionally, they include the effects of both a hot ring current population and a cold plasmaspheric population simultaneously for a geomagnetic storm. The modeled ring current population represents the solution of bounce-averaged kinetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 66 publications
2
47
0
Order By: Relevance
“…This test-particle method has the disadvantage that the particles and fields do not evolve self-consistently. An alternative approach that has been more actively pursued in recent years is to track each source of plasma separately in its own fluid in a multi-fluid MHD model of the magnetosphere (e.g., Glocer et al, 2009Glocer et al, , 2018Glocer et al, , 2020Wiltberger et al, 2010;Winglee et al, 2002). While this methodology does not allow for non-Maxwellian distributions, it does allow for the self-consistent evolution of both plasma and electromagnetic fields.…”
Section: The Ionospheric Plasma Source From a Global Modeling Perspectivementioning
confidence: 99%
“…This test-particle method has the disadvantage that the particles and fields do not evolve self-consistently. An alternative approach that has been more actively pursued in recent years is to track each source of plasma separately in its own fluid in a multi-fluid MHD model of the magnetosphere (e.g., Glocer et al, 2009Glocer et al, , 2018Glocer et al, , 2020Wiltberger et al, 2010;Winglee et al, 2002). While this methodology does not allow for non-Maxwellian distributions, it does allow for the self-consistent evolution of both plasma and electromagnetic fields.…”
Section: The Ionospheric Plasma Source From a Global Modeling Perspectivementioning
confidence: 99%
“…While it might be possible to capture some of these features by imposing convection drifts and a tailward boundary condition on a SAMI2 simulation, a complete numerical description, including zonal convection drifts, are obtainable only via three-dimensional simulation. Ultimately, such modeling will need to be placed into the context of a global magnetosphere simulation, such as by Glocer et al (2020).…”
Section: Discussion: Bottom-up Refillingmentioning
confidence: 99%
“…Several studies have investigated the role of ionospheric sources in populating the plasma sheet. Using test particle motion in global MHD simulation fields (e.g., Huddleston et al, 2005;Moore et al, 2005;Peroomian et al, 2007) or multi-fluid MHD codes (e.g., Glocer et al, 2020;Welling & Ridley, 2010), it was found that global convection was effective in transporting ions of ionospheric origin through the lobes into the PSBL and the plasma sheet, typically at large distances.…”
Section: Discussionmentioning
confidence: 99%